Agriculture for sustainable economic development: A global R&D initiative to avoid a deep and complex crisis - Braun, Joachim von (2008)
World agriculture has entered a new, unsustainable, and politically risky period. Agriculture—and the natural resources it depends on—has been overexploited ecologically, has suffered from underinvestment, has recently been exposed to ill-designed bioenergy programs, and has been politically sidelined for too long. It is now at a critical point. Appropriate responses to the food and agriculture price and productivity crises are lacking. A global initiative for accelerated agriculture productivity is necessary now; such an initiative makes economic sense, is pro-poor and sustainable, and serves security. The initiative needs political leadership and coordination. There is no effective governance architecture at the global level and national levels to address the matter. Industrialized economies, including the United States, should substantially accelerate their investment in international agricultural research and development (R&D) in cooperation with new players.